Pengaruh Arus Kas, Kebijakan Dividen, Dan Pertumbuhan Penjualan Terhadap Harga Saham (Studi Empiris Perusahaan Manufaktur di Bursa Efek Indonesia Tahun2010-2014) - Rini, Erlin Puspita, Eny Kusumawati, SE, MM, AKt, CA (2016)
The function of this research was to examine test the influence of operating cash flow, cash flow, cash flow investment funding, policy dividendand sales growth against the stock price at the manufacturing companies listed on the Indonesia stock exchange in 2012-2014. The population used in this research is manufacturing companies listed in Indonesia Stock Exchange in 2010-2014. The sampling method in accordance with a purposive sampling predetermined criteria. The number of samples collected as many as 124 companies. The research data is secondary data obtained from the Indonesian Capital Market Directory (ICMD) in 2012-2014. The collected data were analyzed using data analysis conducted prior classic assumption test before hypothesis test. Testing the hypothesis in this study using multiple linear regression analysis with t-test, f, and the coefficient of determination. The results showed that the variable cash flow investments, dividend policy and sales growth effect on stock prices. This shows that the cash flow investments, dividend policy and sales growth can affect the height of the low stock prices on manufacturing companies. While operating cash flow and cash flow funding did not affect stock prices. This means high low variable did not have an impact on manufacturing in Indonesia stock exchange.